Base promoted highly efficient copper fluorapatite catalyzed coupling of phenols with arylboronic acids under mild and ligand-free conditions - Mulla, Shafeek Abdul Rashid; Inamdar, Suleman M.; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (RSC Advances, 2012)
A mild, general and highly efficient protocol has been developed for the synthesis of diaryl ethers in good to excellent yield under mild and ligand-free conditions. This is the first example in which a recyclable, heterogeneous copper fluorapatite catalyst is used for the arylation of phenols with arylboronic acids at room temperature in the presence of Cs2CO3 as a base and methanol as a solvent. The catalyst was recovered and reused several times without loss of catalytic activity.

Efficient, rapid synthesis of bis(indolyl)methane using ethyl ammonium nitrate as an ionic liquid - Mulla, Shafeek Abdul Rashid; Sudalai, A.; Pathan, Mohsinkhan Y.; Siddique, Shafi A.; Inamdar, Suleman M.; Chavan, Santosh S.; Reddy, R. Santosh (RSC Advances, 2012)
A simple and rapid protocol has been developed for an efficient synthesis of bis( indolyl)methane in excellent yields using ethyl ammonium nitrate (EAN) as reusable ionic liquid at room temperature. The protocol involves an electrophilic substitution reaction of indoles with several aldehydes.

Ligand free, highly efficient synthesis of diaryl ether over copper fluorapatite as heterogeneous reusable catalyst - Mulla, Shafeek Abdul Rashid; Inamdar, Suleman M.; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (Tetrahedron Letters, 2012)
A novel ligand-free, highly efficient, and an inexpensive method has been developed by using ecofriendly, heterogeneous reusable copper fluorapatite (CuFAP) catalyst for the synthesis of diaryl ethers from the cross coupling reaction of the various substituted aryl halides (fluoride, chloride, bromide, and iodide) with the potassium salts of various substituted phenols in the presence of N-methyl 2-pyrrolidone (NMP) as a solvent at 120 degrees C. The protocol obtained the corresponding cross coupling products in good to excellent yield. The CuFAP catalyst was recovered by simple filtration from the reaction mixture and reused several times without the loss of catalytic activity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arylhalide; Copper fluorapatite; Diaryl ethers; phenol; Ullmann coupling

Novel and efficient synthesis of azaarene-substituted 3-hydroxy-2-oxindoles via sp(3) C-H functionalization of 2-methyl azaarenes and (2-azaaryl)methanes over a heterogeneous, reusable silica-supported dodecatungstophosphoric acid catalyst - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (RSC Advances, 2013)
A novel and efficient protocol has been developed for the synthesis of azaarene-substituted 3-hydroxy-2-oxindoles via sp(3) C-H functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin in good to excellent yield. This is the first example in which heterogeneous, reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) catalyzed sp(3) C-H functionalization of 2-substituted azaarenes and (2-azaaryl)methanes.

Solvent-free, highly efficient one-pot multi-component synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols catalyzed by ethylammonium nitrate as reusable ionic liquid under neat reaction condition at ambient temperature - Mulla, Shafeek Abdul Rashid; Salama, Tarek A.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Chavan, Santosh S. (Tetrahedron Letters, 2013)
A solvent-free, environmentally clean, mild, and simple one-pot multi-component protocol has been developed for the efficient synthesis of 1-amido- and 1-carbamato-alkyl naphthols/phenols in excellent yields via one-pot three-component condensation of various aldehydes, amides/carbamates/urea, and naphthols/phenols using ethylammonium nitrate (EAN) as a reusable ionic liquid catalyst under neat reaction condition at ambient temperature. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; amide; Carbamate Phenol; Ethylammonium nitrate (EAN); Urea

Highly efficient one-pot multi-component synthesis of alpha-aminophosphonates and bis-alpha-aminophosphonates catalyzed by heterogeneous reusable silica supported dodecatungstophosphoric acid (DTP/SiO2) at ambient temperature and their antitubercular eval - Mulla, Shafeek Abdul Rashid; Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Gample, Suvarna P.; Sarkar, Dhiman (RSC Advances, 2014)
A highly efficient one-pot multi-component reaction (MCR) protocol over DTP/SiO2 has been developed for the synthesis of alpha-aminophosphonate derivatives (4a-x) in excellent yields. The alpha-aminophosphonate derivatives were for the first time evaluated for their antitubercular activity against the M. tuberculosis H37Ra (MTB) strain. An evaluation of the data on the cytotoxicity and antimicrobial activity shows that 4n and 4v are promising antitubercular agents.

Ligand-, base-, co-catalyst-free copper fluorapatite (CuFAP) as a versatile, ecofriendly, heterogeneous and reusable catalyst for an efficient homocoupling of arylboronic acid at ambient reaction conditions - Mulla, Shafeek Abdul Rashid; Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Inamdar, Suleman M.; Shaikh, Taufeekaslam M. Y. (RSC Advances, 2015)
This paper describes the first report in which copper species containing copper fluorapatite (CuFAP) acts as a versatile, eco-friendly, recyclable, heterogeneous catalyst for an efficient synthesis of symmetric biaryls from the homo-coupling of arylboronic acids in methanol solvent at ambient reaction conditions. The developed protocol is ligand-, base-, and co-catalyst-free, sustainable, mild, inexpensive, and compatible with a wide range of aromatic/heterocyclic boronic acids and provides the corresponding products in excellent yields without purification. The catalyst was easily recovered from the reaction mixture and reused several times without loss of activity.

Novel one-pot multi-component synthesis of 3,3 `-disubstituted oxindole and spirooxindole scaffolds via Sn-catalyzed C(sp(3))-H functionalization of azaarenes by sequential Knoevenagel-Michael-cyclization reaction - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek Abdul Rashid (RSC Advances, 2015)
Sn-catalyzed C(sp(3))-H bond functionalization of 2-methyl azaarenes/2-(azaaryl)methanes has been achieved for the first time in a one-pot multi-component reaction with isatin and active methylene compounds via tandem sequential Knoevenagel-Michael-intramolecular C-N cyclization. This strategy provides new cost-effective access to potent and biologically/medicinally important spirooxindoles/3,3'-disubstituted 2-oxindoles in good to excellent yields.

Solvent free one-pot multi-component synthesis of beta-azaarene substituted ketones via a Sn-catalyzed C(sp(3))-H functionalization of 2-alkylazaarenes - Chavan, Santosh S.; Pathan, Mohsinkhan Y.; Mulla, Shafeek A. R. (RSC Advances, 2015)
A tin-catalyzed solvent free one-pot multi-component cascade reaction strategy for the direct Michael addition/C(sp(3))-H functionalization of 2-alkylazaarenes with aldehydes and ketones via an aldol reaction has been developed. This is the first report and provides cost effective new access to potent biologically/medicinally important azaarene derivatives with high atom economy.

Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles